Co-Heating method for thermal performance evaluation of closed refrigerated display cabinets. (January 2021) - Månsson, Tommie; Sasic Kalagasidis, Angela; Ostermeyer, York
Abstract: In this study, an application of the adapted Co-Heating methodology for thermal performance evaluation of closed refrigerated display cabinets (RDCs) has been presented. A novel test series comprising three experiments has been developed and demonstrated on a commercial RDC with four doors to evaluate the envelope heat transfer coefficient, thermal inertia, infiltration at idle state and dynamic infiltration caused by door operations. The latter two experiments were conducted in parallel with the condensate collection method for validation of the results for infiltration. It was concluded with good (<10%) conformance between the methods that the infiltration at idle state for the tested RDC is approximately 0.022 kg/s and that one 15 s door opening causes approximately 0.94 kg of ambient indoor air to infiltrate. Additionally, the time, equipment and associated costs for running the tests were compared, and it was concluded that the adapted Co-Heating methodology could substitute the condensate collection method for the evaluation of infiltration while providing additional results on the thermal performance.